BUSINESS STRATEGY ANALYSIS TO ACHIEVE CUSTOMER LOYALTY AMONG TELKOM PROVIDER USERS AT MUHAMMADIYAH SUKABUMI UNIVERSITY - Muhammad Abdul Aziz (Lafadz Jaya Publisher, 2023)
The rapid development of information technology and the increasing use of data communications by users has driven the growth of high-speed internet services. This research aims to analyze the factors that influence increasing customer loyalty, in this case, users of Telkom internet providers at Muhammadiyah University, Sukabumi. The independent variables are service quality, company image and customer satisfaction as mediating variables. The sample of this research was 110 respondents and then they were given a questionnaire to answer. Determination of the sample was carried out by calculations developed by (Hair et al, 1998). That is, the number of samples taken from the population is determined to be 5-10 times the number of indicators. Because in this study there are 24 indicators, the number of indicators is 24 x 6 = 144 respondents. In this study, the respondents were 144 users of the Telkom internet provider at Muhammadiyah University, Sukabumi. The tool used to analyze the data is AMOS 22.00 with the Structural Equation Modeling (SEM) method. The research results show that all of the five hypotheses proposed in this research are acceptable. The factors that have a significant influence are Service Quality and Company Image on Customer Satisfaction and Customer Loyalty. And Customer Satisfaction has a significant positive effect on Customer Loyalty.